Pemetaan Keefektifan Keberadaan Tempat Pengolahan Sampah 3R dalam Mengatasi Masalah Persampahan Di Kabupaten Sleman - Rizki Dwi Gusmawanti; Iswanto Iswanto; Rizki Amalia (Poltekkes Kemenkes Yogyakarta, 2021)
Based on Indonesia Act No. 18 in 2008, waste processing sites with 3R were established to ma-nage household waste. Their existence is needed to be evaluated, one of which is by mapping to understand the local potentiality of waste reduction at each sites. The purpose of this study was to determine the location distribution map, the effectiveness of the 3R sites based on the number of customers, waste reduction, and the service distance range. The method used was spatial analysis that carried out using ArcGis 10.2 application. The study results indicate that there are 20 3R units in Sleman Regency, 50 % has good effectiveness, 40 % has medium effectiveness, and 10 % has less effectiveness. The better the effectiveness of the 3R sites, the greater the number of customers are served. The better the effectiveness of the 3R sites, the higher the ab-sorptive waste capacity of the 3R sites can manage. The limited building of 3R sites in the north and south parts of Sleman Regency needs to be added.